2017
DOI: 10.1002/stem.2735
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Advanced Cell Culture Models for Diamond Blackfan Anemia and Other Erythroid Disorders

Abstract: In vitro surrogate models of human erythropoiesis made many contributions to our understanding of the extrinsic and intrinsic regulation of this process in vivo and how they are altered in erythroid disorders. In the past, variability among the levels of hemoglobin F produced by adult erythroblasts generated in vitro by different laboratories identified stage of maturation, fetal bovine serum, and accessory cells as "confounding factors," that is, parameters intrinsically wired in the experimental approach tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Analysis of cKIT metabolism identified the critical role played by CD63 in favoring endocytosis of cKIT, and therefore in quenching its signaling, in adult cells. In spite of the well-described effects of SCF on erythropoiesis, clinical attempts to use this growth factor for the treatment of EPO-unresponsive anemias have not been encouraging so far and an international trial in Diamond Blackfan Anemia was prematurely interrupted by the National Institute of Health after the death of one patient (58). Our observations suggest that CD63 antibodies, by neutralizing CD63, may prolong the canonical signaling of cKIT at physiological SCF levels increasing the expansion of the adult erythroid pool and.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cKIT metabolism identified the critical role played by CD63 in favoring endocytosis of cKIT, and therefore in quenching its signaling, in adult cells. In spite of the well-described effects of SCF on erythropoiesis, clinical attempts to use this growth factor for the treatment of EPO-unresponsive anemias have not been encouraging so far and an international trial in Diamond Blackfan Anemia was prematurely interrupted by the National Institute of Health after the death of one patient (58). Our observations suggest that CD63 antibodies, by neutralizing CD63, may prolong the canonical signaling of cKIT at physiological SCF levels increasing the expansion of the adult erythroid pool and.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired translation or transcription of the master erythroidmegakaryocyte (MK) transcription factor GATA1 (11) due to defective ribosome biogenesis (12) and excess heme toxicity (13,14) has been suggested as a unifying mechanism of erythroid failure across DBA genotypes. However, inconsistent findings from human model cellular systems and cell lines (4,(14)(15)(16)) are yet to be reconciled, and it remains unclear whether additional mechanisms may contribute to erythroid failure in DBA (17). Furthermore, although the diagnostic criteria of DBA include presentation in infancy with virtually no mature bone marrow erythroblasts (EBs) (3), atypical presentations in later life with milder hematological manifestations are not uncommon (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…While ex vivo culture from HSCs reproduces aspects of normal erythropoiesis and provides a source of erythroid cells to study, a number of confounding factors have been identified that make interpretation of the data difficult. 14,38 Therefore, in order to investigate differences between patient-derived erythroblasts and those from healthy controls we took extreme care to stage the cultures using an array of methods that included FACS and CyTOF, which both rely on immunophenotyping cell populations. While such methods showed healthy and diseased erythroblasts were immunologically similar during the expansion phase and into early differentiation, aspects of disordered erythropoiesis became evident after this time by several parameters.…”
Section: Discussionmentioning
confidence: 99%